2016
DOI: 10.1002/2016ef000381
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of methane emissions in cities: How new measurements and partnerships can contribute to emissions reduction strategies

Abstract: Cities generate 70% of anthropogenic greenhouse gas emissions, a fraction that is growing with global urbanization. While cities play an important role in climate change mitigation, there has been little focus on reducing urban methane (CH 4 ) emissions. Here, we develop a conceptual framework for CH 4 mitigation in cities by describing emission processes, the role of measurements, and a need for new institutional partnerships. Urban CH 4 emissions are likely to grow with expanding use of natural gas and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 96 publications
0
36
0
Order By: Relevance
“…Such loss rates are expensive, locally potentially dangerous, and an unnecessary greenhouse emission. Yet currently many jurisdictions pay little attention to mitigating urban gas leaks: for example, in the United States, Hopkins et al () concluded that “current mitigation approaches are absent or ineffective.” Even safety can be neglected. A recent example is the series of explosions and fires in the Merrimack valley, Massachusetts, USA, in September 2018 that killed one person and damaged over a hundred buildings (NTSB, ).…”
Section: Practical Emission Reduction and Removal—tractable Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such loss rates are expensive, locally potentially dangerous, and an unnecessary greenhouse emission. Yet currently many jurisdictions pay little attention to mitigating urban gas leaks: for example, in the United States, Hopkins et al () concluded that “current mitigation approaches are absent or ineffective.” Even safety can be neglected. A recent example is the series of explosions and fires in the Merrimack valley, Massachusetts, USA, in September 2018 that killed one person and damaged over a hundred buildings (NTSB, ).…”
Section: Practical Emission Reduction and Removal—tractable Emissionsmentioning
confidence: 99%
“…Such loss rates are expensive, locally potentially dangerous, and an unnecessary greenhouse emission. Yet currently many jurisdictions pay little attention to mitigating urban gas leaks: for example, in the United States, Hopkins et al (2016) concluded that "current mitigation approaches are absent or ineffective." Even safety can be neglected.…”
Section: Urban Gas Leaksmentioning
confidence: 99%
“…Production‐based emission accounting (PBA) represents the on‐site emissions within national territory (sometimes referred to as territorial‐based) preferred by the UNFCCC. Existing studies whether regarding national, regional, and sectoral CH 4 emissions are all in the scope of PBA circumstance (e.g., Du et al, ; Höglund‐Isaksson, ; Hopkins et al, ; Janssens‐Maenhout et al, ; B. Zhang, Chen, et al, ). But GHG emissions from various industrial sectors are induced by economic behaviors (Oliveira & Bourscheidt, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many wastewater treatment plants also use anaerobic digesters which collect CH 4 for eventual combustion, but may have fugitive CH 4 emissions. Of the urban sources of CH 4 , this source is perhaps the most uncertain (Hopkins et al, 2016a). For the purposes of this study, we assume CH 4 emissions are most likely to arise from the plants with the largest daily flow capacity; however, emissions could also potentially arise from various points of collection and/or drainage of wastewater and sewage.…”
Section: Domestic and Industrial Wastewater Treatment And Discharge (mentioning
confidence: 99%
“…We chose the IPCC approach because it is more standardized, and hence applicable to other cities. The lifecycle approach requires local knowledge, and is likely to differ among cities and regions (Hopkins et al, 2016a). We also assumed that most CH 4 emissions come from the main facility associated with an emitting activity, such as wastewater treatment plants for wastewater emissions, rather than the sewer network.…”
Section: Vista-la Data Completeness and Uncertaintymentioning
confidence: 99%